Sliding mode control for networked control systems: A brief survey - Zhou, Weixiang; Wang, Yueying; Liang, Yinzheng (ISA transactions, 2022)
In recent years, the control synthesis and analysis of networked control systems (NCSs) have attracted increasing attention from both industrial and scientific communities, and many contributions have been published. With the development of advanced control theories, it has become a trend to combine networks with control systems. As a specific nonlinear control method, due to its complete robustness on the sliding mode surface, sliding mode control (SMC) becomes an effective means to solve the uncertainties and nonlinear characteristics in NCSs. In this paper, a review of the recent advances and challenges of SMC in NCSs is given. Firstly, a brief introduction to NCSs is given and the essential technical constraints are also summarized. Then, the results of the SMC applied to NCSs with basic constraints, including packet dropouts, time delays and signal quantization are given in details. Finally, some concluding remarks are made and several potential future research topics are discussed.